Implementasi House of Risk (HOR) dan Root Cause Analysis dalam Strategi Mitigasi Risiko Kegagalan Mesin Produksi pada PT Industri Kereta Api - Persada, Ikhlas Damai; SZS, Joumil Aidil (Universitas Nahdlatul Ulama Blitar, 2025)
PT Industri Kereta Api or commonly called PT INKA is a company engaged in the field of railway production. One of the machines that often experiences damage is the Gap Shear / Hydraulic Shear machine, with a total of 41 repairs during the period June 2023 to February 2024. From this problem it is necessary to carry out an analysis using the House of Risk (HOR) method and Root Cause analysis to determine optimal risk mitigation strategies so as to minimize the occurrence of machine damage. The results of the research recommend that companies can monitor and analyze the service life of machine components based on the intensity of machine use, implement a production scheduling system and apply predictive analysis of safe production quantities for machine reliability, implement regular training programs for operators regarding instructions and standards for machine use and create a clear and easy to understand machine usage manual, provide clear documentation regarding the materials used and their characteristics, and implement preventive maintenance based on vibration monitoring data.